The Mosque of Kagungan Dalem Sulthony Rejodani - Muhammad Wildan; Azis Azis (Millati: Journal of Islamic Studies and Humanities)
Yogyakarta Sultanate until recent days has quite a number of mosques, namely Kagungan Dalem Mosques. Each mosque records some historical accounts on the concern of Yogyakarta Sultanate to Islam and also faces modern values. The mosque of Kagungan Dalem Sulthony which is located at Rejodani Sleman is an interesting site to study. Its history traces back to the period of Prince Diponegoro and extends to the period of Indonesian Independence. Furthermore, its significance is underpinned by its location in Rejodani, renowned as a religious village with strong cultural ties to the moderate Muhammadiyah movement. Today, this mosque has encountered intriguing challenges that transcend cultural and ideological dimensions. To strengthen the cultural identity of Muhammadiyah in the Rejodani village within an increasingly pluralistic society, it grapples with ideological contestation emanating from Nahdlatul Ulama (NU), Salafis, and various other groups. This article seeks to delve into the abovementioned issues through an anthropological lens, employing participatory and ethnographic research methods. Additionally, this article examines the conflict between conservatism and modernism within the Kagungan Dalem mosque.